Direct regeneration and rapd assessment of male inflorescence derived plants of musa cuminata cv. berangan - Harirah, A.A.; Khalid, Norzulaani (Malaysian Society for Molecular Biology and Biotechnology, 2006)
Regenerated plants were established using male inflorescence of Musa acuminata cv. Berangan. Explants were cultured on Murashige and Skoog (MS) solid medium supplemented with three different concentrations of 6-benzylaminopurine (BAP). After 2 weeks, whitish bud-like structures (WBLS) were obtained and MS media supplemented with 70.0 Î¼M BAP was observed as the best media for the growth of WBLS. After 3 months, shoot-like structures emerged and MS media supplemented with 31.0 Î¼M BAP gave a large number of shoot formation. Normal looking plantlets were obtained within 4 - 6 months with an average of 80 - 130 shoots regenerated from each male inflorescence. Random amplified polymorphic DNA (RAPD) was carried out to determine the clonal fidelity on in vitro Musa acuminata cv. Berangan micropropagated from male inflorescence derived from the same mother plant. Eighteen arbitrary decamer primers were used to amplify DNA from in vitro plants materials. All RAPD profiles from regenerated plants were monomorphic thus no somaclonal variation was detected. A total of 81 bands were scored from PCR amplification of genomic DNA from 15 micropropagated plants. This was further confirmed by the value of similarity index which was equaled to 1. This result implied that male inflorescence could be used as an alternative explant for commercial planting.